Bagaimana Subjective Norms dan Entrepreneurship Education Berpengaruh Terhadap Entrepreneurial Intention Mahasiswa? - Unang Toto Handiman; Herdiyanto Herdiyanto; Dinar Nur Affini; Ahmad Faridi; Ahmad Hidayat Sutawijaya (Jurnal Doktor Manajemen (JDM), 2022)
The higher the number of entrepreneurs in a country, the higher the economic growth and development rate. What can be done to increase the number of entrepreneurs? Can entrepreneurship be created? This study aimed to measure the effect of Subjective Norms and Entrepreneurship Education on the Entrepreneurial Intention of students. The samples of this study were students of the Faculty of Economics and Business, Mercu Buana University, Meruya Jakarta campus, and Kranggan Bekasi. This research category is the quantitative method. Researcher collected data by distributing questionnaires using the snowball technique via a google form—measurement of data using statistical model SPSS and Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that: (1) SN has a direct effect on ATB and PBC. (2) SN has an indirect influence on EI through ATB and PBC. (3) EE can moderate the impact of ATB, SN, PBC on EI. (4) SN, ATB. PBC and EE have a direct influence on EI. The novelty of this study is that the combination of SN and EE can generate student EI, whereas some previous research findings indicate that SN does not significantly affect EI.Keywords: Entrepreneurship Education, Attitude Toward Behavior,